2001
DOI: 10.1135/cccc20011729
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Underivatized Brassinosteroids by HPLC/APCI-MS. Occurrence of 3-Epibrassinolide in Arabidopsis thaliana

Abstract: In the course of investigations on brassinosteroid (BS) biosynthetic and metabolic pathways in plants, an approach using HPLC/APCI-MS analysis of underivatized BS for their identification in plant material has been developed. Its application to root-callus suspension cultures of Arabidopsis thaliana led to the first identification of 3-epibrassinolide as natural brassinosteroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The obtained compounds were used for biosynthetic studies. Three new brassinosteroids were identified in these experiments, including 3‐epibrassinolide in Arabidopsis thaliana ,27 secasterol and 2,3‐diepisecasterone in Secale cereale 28. A new biosynthetic subpathway from typhasterol/teasterone via 2,3‐epoxybrassinosteroids to castasterone was found in seedlings of S. cereale 29.…”
Section: Discussionmentioning
confidence: 81%
“…The obtained compounds were used for biosynthetic studies. Three new brassinosteroids were identified in these experiments, including 3‐epibrassinolide in Arabidopsis thaliana ,27 secasterol and 2,3‐diepisecasterone in Secale cereale 28. A new biosynthetic subpathway from typhasterol/teasterone via 2,3‐epoxybrassinosteroids to castasterone was found in seedlings of S. cereale 29.…”
Section: Discussionmentioning
confidence: 81%
“…An analytical method previously developed in our laboratory10 used the atmospheric pressure chemical ionization (APCI) inlet for the ionization. The lowest LOD achieved was only 10 ng μL −1 , far below the sensitivity needed for biosynthetic studies of plant‐derived BS using deuterium‐labeled precursors.…”
Section: Resultsmentioning
confidence: 99%
“…traditionally play an important role in this research field as well, but are not suitable for biosynthetic studies. More recently, high‐performance liquid chromatography (HPLC) and liquid chromatography/mass spectrometry (LC/MS) analyses of free10 or derivatized BS11,12 were introduced. A fluorescent tagging of BS with dansyl‐3‐aminophenylboronic acid improved the limit of detection (LOD) down to the femtomolar (fmol) range 13…”
mentioning
confidence: 99%
“…The reverse conversion of 3-epicastasterone and 2-epicastasterone to castasterone was detected recently in seedlings of Secale cereale [10]. The conversion of brassinolide to 3-epibrassinolide, a naturally occurring brassinosteroid in Arabidopsis [24], and the reverse conversion are reported here for the first time and, together with the corresponding conversions between castasterone and 3-epicastasterone, are discussed in the context of hormone homeostasis in plants.…”
Section: Introductionmentioning
confidence: 93%
“…In A. thaliana, brassinosteroids [25 -26] have been reported several times [27 -29]. Castasterone (1) and brassinolide (2) are native also to Arabidopsis shoots and seeds, and 3-epibrassinolide (4) was recently found in root-callus suspension cultures of ecotype C24 [24]. Schmidt et al [30] reported castasterone (1) together with other brassinosteroids from seeds of S. cereale.…”
Section: Brassinosteroids In Arabidopsis Thaliana and Secale Cerealementioning
confidence: 99%